An electricity-fluorescence double-checking biosensor based on graphene for detection of binding kinetics of DNA hybridization. Issue 70 (15th September 2017) - Yue, Weiwei; Tang, Caiyan; Wang, Chunxing; Bai, Chengjie; Liu, Shuyi; Xie, Xiaohui; Hua, Hongling; Zhang, Zhen; Li, Dengwang
Abstract : In this paper, an electricity-fluorescence double-checking biosensor based on graphene materials has been presented for detection of DNA hybridization kinetics. Abstract : In this paper, the study of an electricity-fluorescence double-checking biosensor and detection system has been presented. The fabrication of the double-checking biosensor was performed by integrating graphene field effect transistors (GFETs) and biosensors based on fluorescence resonance energy transfer (FRET). For the construction of the GFETs as an electrical detection channel, graphene films grown by chemical vapour deposition (CVD) were transferred onto glass substrates. A probe aptamer modified with 6′-carboxy-fluorescein (6′-FAM) was immobilized on the graphene film of the GFETs via 1-pyrenebutanoic acid succinimidyl ester (PBASE) following which graphene oxide (GO) was used to quench the 6′-FAM on the probe aptamer to form the fluorescence detection channel. When the complementary target DNA (tDNA) was introduced into the GFETs, it replaced the GO and was hybridized with the probe aptamer leading to restoration of the fluorescence of the probe aptamer. At the same time, the tDNA hybridized with the probe aptamer leading to the formation of a new double conductive layer of the GFETs, which could change the conductivity of the GFETs. With a home-made double channel detection system, the dynamic hybridization process of the tDNA with the probe aptamer was achieved simultaneously through the electrical and fluorescence channels. Compared with conventional biosensors that are equipped with a single detection mode, this double-checking biosensor could be used to monitor the time and concentration-dependent DNA hybridization kinetics in a reliable and sensitive manner. Furthermore, this work also provides a new strategy for designing biosensors integrated with multiple sensing techniques.